Parvovirus B19 seroprevalence, viral load, and genotype characterization in volunteer blood donors from southern Brazil. Issue 7 (25th March 2019) - Slavov, Svetoslav N.; Rodrigues, Evandra S.; Sauvage, Virginie; Caro, Valérie; Diefenbach, Cristiane F.; Zimmermann, Ana M.; Covas, Dimas T.; Laperche, Syria; Kashima, Simone
Abstract: Usually transmitted via respiratory droplets, parvovirus B19 (B19V) can also be acquired by blood transfusion especially because of viral persistence, resistance to blood treatment procedures, and high viral load during the early infection phase. This is particularly problematic in immunocompromised or anemic patients where the infection can have a severe outcome. As B19V DNA was detected in blood donations from South Brazil during a viral metagenomic survey performed by Next‐Generation Sequencing, the objective of this retrospective study was to evaluate the seroprevalence, B19V DNA presence and circulating genotypes in a Hospital Blood Transfusion Service in Santa Maria city in South Brazil (Rio Grande do Sul state). Among 480 volunteer blood donors, 53.9% ( n  = 258 of 479) were anti‐B19V IgG‐positive, and 9 (1.9%) plasma samples presented B19V DNA. In almost all cases ( n  = 7 of 9, 77.8%), B19V DNA load was accompanied by the presence of anti‐B19V IgG suggesting a persistent infection. The sequencing of the strains demonstrated that all belong to genotype 1 which is the most prevalent worldwide. The analysis of the recipient information of the positive for B19V DNA units revealed no related posttransfusion adverse effects. Our results demonstrate for the first time, B19V seroprevalence, viral load, and genotypes among blood donors from South Brazil and give a light for the circulation and impact of this B19V in this part of the country.